Psychometric properties of a Romanian translation of the Functionality Appreciation Scale (FAS). (June 2021) - Swami, Viren; Todd, Jennifer; Goian, Cosmin; Tudorel, Otilia; Barron, David; Vintilă, Mona
Highlights: Scores on Romanian Functionality Appreciation Scale (FAS) are 1-dimensional. Romanian FAS scores have adequate test-retest reliability and construct validity. Romanian FAS scores are invariant across sex, but sex difference in latent scores were null. Abstract: The Functionality Appreciation Scale (FAS; Alleva et al., 2017) is a 7-item measure of an individual's appreciation of their body for what it can do and is capable of doing. Although the instrument is increasingly used in interventionist studies, its psychometric properties have been infrequently investigated outside Anglophone populations. Here, we examined psychometric properties of a novel Romanian translation of the FAS. An online sample of 959 Romanian adults (18–73 years old) completed the Romanian FAS, and validated measures of positive body image (body appreciation), negative body image (weight discrepancy in women, drive for muscularity in men), eating disorder symptomatology, and psychological well-being (self-esteem, gratitude). Exploratory factor analyses led to the extraction of a 1-dimensional model of FAS scores, which we confirmed using confirmatory factor analysis. FAS scores achieved scalar invariance across sex, but the sex difference in latent FAS scores did not reach significance (d = 0.15). FAS scores had adequate internal consistency and test-retest reliability up to four weeks, and further analyses provided evidence of convergent, construct, and incremental validity. These results support the psychometric properties of the Romanian FAS and present evidence of the importance of functionality appreciation in relation to healthier body image and psychological well-being.